2019
DOI: 10.1111/coa.13335
|View full text |Cite
|
Sign up to set email alerts
|

Immunity‐targeted approaches to the management of chronic and recurrent upper respiratory tract disorders in children

Abstract: BackgroundUpper respiratory tract infections (URTIs), including rhinitis, nasopharyngitis, tonsillitis and otitis media (OM), comprise of 88% of total respiratory infections, especially in children. Therefore effective prevention and treatment of RTIs remain a high priority worldwide. Preclinical and clinical data highlight the rationale for the use and effectiveness of immunity‐targeted approaches, including targeted immunisations and non‐specific immunomodulation in the prevention and management of recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 82 publications
1
12
0
6
Order By: Relevance
“…OM-85 has been recommended as adjunct medication to standard medical treatment in adults with CRS without polyps [48,49] and was mentioned in a recently published consensus paper as an effective product to prevent RTIs in children [50]. A recent systematic review concluded that OM-85 can be considered a promising and additional tool in the limited armamentarium of the ENT physician dealing with paediatric ENT infections and their complications [51].…”
Section: Discussionmentioning
confidence: 99%
“…OM-85 has been recommended as adjunct medication to standard medical treatment in adults with CRS without polyps [48,49] and was mentioned in a recently published consensus paper as an effective product to prevent RTIs in children [50]. A recent systematic review concluded that OM-85 can be considered a promising and additional tool in the limited armamentarium of the ENT physician dealing with paediatric ENT infections and their complications [51].…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent studies recommend more randomized controlled trials with adequate long-term follow-up to clarify the benefits of tonsillectomy versus non-surgical treatment in patients with recurrent tonsillitis. 9 Drugs such as penicillin and Azithromycin (AZT) are widely used to control recurrent tonsillitis.…”
Section: Introductionmentioning
confidence: 99%
“…Дефицит IgG 3 , который может протекать совместно с дефицитом IgG 1 , связывают с рецидивирующими обструктивными заболеваниями легких [2,3]. Рецидивирующие респираторные инфекции бактериальной этиологии (гемофильная палочка, пневмококк) имеют связь с дефицитом IgG 2 в ассоциации с дефицитом IgA [11,12].…”
Section: Introductionunclassified
“…Цель исследования -провести анализ содержания иммуноглобулинов в крови и слюне у детей 2-16 лет и характер их взаимосвязей в зависимости от возраста ребенка и частоты эпизодов ОРВИ. [12,13] у 50% часто болеющих детей повышен уровень общего IgE (160-220 МЕ/мл), что соответствует и нашим данным (48,6%). При ОРВИ в год более 6 раз отмечается сниженный уровень IgA в сыворотке.…”
Section: Introductionunclassified